2012
DOI: 10.1002/hed.21946
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary reconstruction using the scapular tip free flap: A radiologic comparison of 3D morphology

Abstract: Based on this analysis, there is close similarity between the shapes of the palate and the scapular tip. This similarity supports use of the scapular tip flap for selected palate defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The STFF has additional advantages over the traditional lateral bone scapular border free flap, with increased pedicle length and morphological similarity to the native mandible angle, maxilla, and palate. These improvements facilitate a reduced rate of vein grafting during revascularization of the flap, and make delicate flap fabrication possible without additional osteotomies [ 5 6 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The STFF has additional advantages over the traditional lateral bone scapular border free flap, with increased pedicle length and morphological similarity to the native mandible angle, maxilla, and palate. These improvements facilitate a reduced rate of vein grafting during revascularization of the flap, and make delicate flap fabrication possible without additional osteotomies [ 5 6 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The entire hemi-maxilla -including the orbital floor and the palate-might be completely reconstructed if the flap is positioned vertically. Moreover, the flap can reproduce the entire palato-aveolar complex when it is oriented horizontally 13 . Another important advantage of this flap is its reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the bone can be ''greenstick''-fractured to guarantee a proper set-in and adequate projection. In contrast to fibula, no further osteotomies need to be performed for the proper set in 13 . The fixation of the bone may be accomplished with the use of miniplates or wire.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, postoperative computed tomography assessment of the scapular tip demonstrated the similarity in shape of the scapula to the palate-a common reason and support for using this flap in palatomaxillary reconstructions. 38,74 The scapula tip is considered ideal for reconstruction of the palatal shelf, and multiple skin paddles can be harvested to line both the oral and sinonasal cavities. 75 Clark et al reported on experience of patients undergoing maxillectomy and scapular tip reconstruction.…”
Section: Scapula Free Flapmentioning
confidence: 99%